The forensic aesthetic in art - Spargo, Natascha (Rhodes University, Faculty of Humanities, Department of Fine Art, 2006)
From Introduction: The 'forensic aesthetic' presents the viewer with traces and debris - the residue that haunts sites of transgression, violence and death. In his book Scene of the Crime, art critic and curator Ralph Rugoff (1997:62) defines the forensic aesthetic as follows: "Inextricably linked to an unseen history, this type of art embodies a fractured relationship to time. Like a piece of evidence, its present appearance is haunted by an indeterminate past, which we confront in the alienated form of fossilized and fragmented remnants." Through its play on seemingly insignificant detail&, clues and traces, the forensic aesthetic suggests that meaning is dispersed, fragmentary and uncertain. According to Rugoff (1997:17), the forensic aesthetic "aims to engage the viewer in a process of mental reconstruction". It compels the viewer to adopt a 'forensic gaze' : to sift through broken narratives and fragments of information, reading the artwork as one might read a sample of evidence. Rugoff (1997:62) argues that: "[S]uch art insists that 'content is something that can't be seen' ... it requires that the viewer arrive at an interpretation by examining traces and marks and reading them as clues. In addition, it is marked by a strong sense of aftermath. ... Taken as a whole, this art puts us in a position akin to that of [the] forensic anthropologist or scientist, forcing us to speculatively piece together histories that remain largely invisible to the eye." One might argue that some of the earliest known examples of the forensic aesthetic in art presented themselves in the Renaissance period in the form of the pseudo-forensic anatomical drawings of Leonardo da Vinci. In his Studies of the Hand (fig. 1), for example, Da Vinci methodically represents the underlying structures of the human hand in a series of drawings that are scattered intermittently across the page. The remainder of the page is covered with hand-written notations. In this work, the artist approaches the human body with a scientific, almost forensic, gaze. Here the body is presented in fragments, rather than as a whole. According to Rugoff (1997:86&88), the forensic aesthetic addresses the body "not as a coherent whole but as a site of prior actions ... as a dispersed territory of clues and traces". When read in terms of the mode of the forensic aesthetic, Da Vinci's Studies of the Hand may be said to look at the human body as forensic object. In this way, this work may be said to speak of the manner in which the forensic gaze operates in the context of the artwork. Throughout the following essay, I discuss the various ways in which the forensic aesthetic manifests itself in art. I have necessarily been selective in the artworks that I have chosen for discussion, as this topic is very broad indeed. In Chapter One, I explore the tradition of the forensic aesthetic in art by way of a select number of artworks. This chapter focuses on investigating the way in which these works, whether consciously or unconsciously, speak of associations between violence and representation through the mode of the forensic aesthetic. The contents of Chapter Two concentrate on the work of South African artist Kathryn Smith. Smith's work may be said to possess a forensic quality, in that it references forensic practices and techniques. Her work has not been the topic of a lengthy monograph, but it has been considered in various exhibition catalogues, reviews and articles. For example, an essay by Colin Richards entitled 'Dead Certainties' (2004) investigates the forensic quality of Smith's imagery in terms of its play on notions of the trace. Similarly, an article by Maureen de Jager, entitled 'Evidence and Artifice' (2004), examines the manner in which Smith's work transgresses the boundaries between 'forensics and fantasy'. In her book, Through the Looking Glass (2004), Brenda Schmahmann addresses Smith's Still Life series (figs. 9, 10, 11) in relation to the issue of self-representation, exploring the relationship between the 'self' and the body as 'other'. Lastly, a review by James Sey, which was published in Art/South Africa (2004), considers Smith's work in terms of its aesthetic appeal, which serves as a framing device for the uncomfortable subject matter that informs the bulk of her imagery. My reading of Kathryn Smith's work departs from and expands on the available literature in that it focuses on the manner in which her images comment self-critically on the act of representation. I have chosen to focus on Smith's work in particular, as it uses the mode of the forensic aesthetic to speak of the field of artistic practice - a motif that runs throughout my own body of work as well. Moreover, Smith's work, like my own work, may be said to engage with the forensic aesthetic in a South African context. In Chapter Two, I compare a number of Smith's works to the artworks discussed in Chapter One, and examine the manner in which they speak of the links between art and crime. Chapter Three concentrates on outlining the ways in which my own work reads off the conventions of forensic investigation. In this chapter I discuss the manner in which my work, by way of a forensic approach, draws parallels between the medium of photography and the mechanisms of trauma. I focus on works that have been included in my Master's exhibition, Vigil (2005). The following essay is a study in representations of violence in art. In the course of this essay, I contextualize the forensic aesthetic as a mode of representation, as well as address the manner in which the forensic aesthetic seems to allow for, even facilitate, self-conscious reflection on the practices of representation itself.
Keywords: Violence in art; Psychic trauma -- Pictorial works; Aesthetics; Human figure in art; Smith, Kathryn, 1975-